Revealing the hidden diversity of Chlorella heliozoae-infecting giant viruses - Lethícia R. Henriques; Bruna B. F. Botelho; Roger M. Carlson; João Victor R. P. Carvalho; Ellen G. Oliveira; Irina V. Agarkova; James L. Van Etten; David D. Dunigan; Rodrigo A. L. Rodrigues (npj Viruses)
Abstract A new level of viral complexity has emerged from the isolation of green algae-infecting chloroviruses from diverse aquatic environments around the world over the past few decades. This study focuses on describing and comparing the genomic features of gammachloroviruses, previously referred to as SAG-viruses. We present 24 novel isolates capable of forming plaques on lawns of Chlorella heliozoae SAG 3.83, including the first giant virus isolated from Greenland. Together with 13 previous isolates, these new viruses form a robust dataset that we used to investigate the genomic landscape and to test whether environmental conditions influence the species diversity of gammachloroviruses. Genome sizes range from 283 kbp to 385 kbp, with one new isolate having the smallest genome found in the genus Chlorovirus. Based on phylogenomics and global genome identity analysis, we defined 10 species of “Gammachlorovirus”, half of which are represented by a single isolate. We observed a high level of genome synteny, and the tRNA islets maintain a distinct interspecific pattern, although some notable variations are evident. Our analysis reveals an open pan-genome composed of 681 COGs, more than 30% of which consist of uncharacterized genes, highlighting significant innovative genetic potential for these viruses. Our results suggest that the subgenus “Gammachlorovirus” exhibits the greatest genetic diversity among chloroviruses, with variability that is independent of geographic location. Overall, these findings underscore the considerable diversity within these ten newly defined species and the importance of isolating and characterizing chloroviruses from new locations worldwide to enhance our understanding of the ecology and evolution of this group of giant algal viruses.